P49 LncRNA-mRNA co-expression involved in high risk HPV-related cervical cancer cells. (1st November 2019) - Yang, L; Zeng, X; Xi, M
Abstract : Introduction/Background: Long non-coding RNAs are emerging to be novel regulators in gene expression. In current study, lncRNAs microarray and lncRNA-mRNA co-expression analysis were performed to explore the alternation and function of lncRNAs in cervical cancer cells. Our study might help to understand the interplay between lncRNAs and coding genes anticipated in oncogenic HPV proliferation, and lncRNAs may be the missing links of well-known oncogenic and tumor suppressor networks. Methodology: The high-throughput analysis was performed to detect the global lncRNAs and mRNAs expression changes between oncogenic HPV-positive cervical cancer cells (SiHa and HeLa) and oncogenic HPV-negative cervical cancer cells (C33-A). Additionally, we constructed a co-expression network of lncRNAs and coding gene transcripts to predict and validate the potential biological function of differentially expressed lncRNAs. Western blot, PCR and transwell test were performed to validate the biological function of ENST00000420168, ENST00000564977 and TCONS_00010232 in cervical cancer cells. Results: With the help of mRNA-lncRNA co-expression network, we found that ENST00000503812 was significantly correlated with RAD51B and IL-28A expression in HPV-16 positive cervical cancer cells (SiHa), while ENST00000420168, ENST00000564977 and TCONS_00010232 had significant correlation with FOXQ1 and CASP3 expression in HPV-18 positive cervical cancer cells (HeLa). Up-regulation of ENST00000503812 inhibited RAD51B and IL-28A expression and result in deficiency of DNA repair pathway and immune responses in HPV-16 positive cervical cancer cells. Up-regulation of ENST00000420168, ENST00000564977 and down-regulation of TCONS_00010232 stimulated FOXQ1 expression and suppressed CASP3 expression in HPV-18 positive cervical cancer cell, which leads to HPV-induced proliferation and deficiency in apoptosis. Conclusion: Our study demonstrated that integration of oncogenic HPV DNA into host genome could alter the expression profiles of lncRNAs in cervical cancer cells. Co-expression network revealed that certain lncRNAs can lead to differentially expression of their target coding genes including several crucial regulators of DNA repairing, cell cycle, proliferation and apoptosis in HPV-positive cervical cancer cells. Disclosure: Nothing to disclose.